CircHIPK3 negatively regulates autophagy by blocking VCP binding to the Beclin 1 complex in bladder cancer - Chong Wang; Tiantian Liu; Jiawei Wang; Chao Cheng; Ze Zhang; Jingwei Zhang; Houbao Huang; Yawei Li (Discover Oncology, 2023)
Abstract Circular RNA HIPK3 (circHIPK3) mediates the progression of multiple cancers, including bladder cancer, by regulating cell migration, autophagy and epithelial mesenchymal transition. However, the mechanism by which circHIPK3 regulates autophagy in bladder cancer cells remains unclear. Autophagy is a common self-protection mechanism in eukaryotic cells and is essential for cell survival and death regulation. However, it is unclear whether circHIPK3 affects the level of autophagy in bladder cancer through binding proteins, and the potential regulatory mechanism is unknown. Here, we found that circHIPK3 levels were significantly lower and autophagy-related proteins were significantly upregulated in bladder cancer cells and tissues compared to normal controls. CircHIPK3 downregulation promoted bladder cancer cell proliferation, while circHIPK3 overexpression inhibited proliferation. CircHIPK3 overexpression significantly suppressed autophagy in bladder cancer cells. Overexpression of circHIPK3 did not affect VCP protein expression but inhibited the VCP/Beclin 1 interaction. VCP also stabilized Beclin 1 and promoted autophagy in bladder cancer cells by downregulating ataxin-3. Thus, circHIPK3 may play an important role in bladder cancer by inhibiting VCP-mediated autophagy.